Differential expression of P63, P27, P57, Ki-67, and CD146 in hydropic and molar pregnancies - Mahi Balci; Gulhan Ozdemir; Admin (Journal of the Pakistan Medical Association, 2021)
Objective: In this study, we investigated expressions of immunohistochemical markers P63, P27, P57, Ki-67, and CD146, in hydropic and molar specimens, to explore their role in pathogenesis of molar gestations. Design and Setting: Retrospective study. Methods: We enrolled 37 patients with a definitive pathologic diagnosis of HA (n = 10), PHM (n = 17), and CHM (n = 10). We scored immunoreactivity using antibodies against P63, P27, P57, Ki-67, and CD146 by evaluating the percentage of distinctly stained cells. Results.Compared to PHM and HA patients, CHM patients had severe cytologic atypia in CD146-positive extravillous trophoblastic column (TC) and florid syncytiotrophoblast (ST) proliferation. P57 immunostaining was negative in all but one of the CHM patients, whereas all HA and PHM patients showed positive immunostaining. PHM and HA patients also showed P63 and Ki-67 overexpression in cytotrophoblasts (CTs) compared to CHM patients. P27 was expressed in differentiated, nondividing syncytiotrophoblasts but did not yield any diagnostic aid. Conclusion: The proliferative activity location varied between molar and nonmolar pregnancies. PHM and HA patients have more progenitor cells, which express the highest levels of P63 compared to CHM patients. The loss of endogenous P63 expression in CHM cases may result in up-regulated genes, associated with invasion and metastasis, predisposing the body to a loss of epithelial and acquisition of mesenchymal characteristics.P63 deficiency, like P57 deficiency, induces exaggerated proliferation and differentiation and could be used as an ancillary diagnostic tool for CHM diagnosis. Keyword: Hydatidiform mole, hydropic abortion, p63, p27, p57, Ki-67, CD146. Continuous...